Analisis Kinerja Pengelolaan Dana Operasional Sekolah (BOS) pada SD GMIT 07 Oebufu - Omega Ch Riwu; Anthon S.Y Kerihi; Cicilia A. Tungga (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research aims to determine the management of School Operational Assistance (BOS) funds at GMIT 07 OEBUFU Elementary School based on the POAC Planning, Organizing, Implementing and Accountability management system. This research uses a qualitative descriptive research type using the Nvivo tool. The data sources used are primary data sources and secondary data sources with data collection techniques based on the results of interviews, observation, documentation and triangulation. The data analysis techniques used are data reduction, data presentation and drawing conclusions using the N-vivo 12 Plus software tool. The research results show that the performance of managing School Operational Assistance (BOS) funds at GMIT 07 Oebufu Elementary School is based on the Planning, Organizing, Implementing and Accountability (POAC) management system. The performance of managing school operational funds has been running quite well, however, in the process of managing boss funds, there are problems at the implementation stage where the school experiences delays in disbursement due to delays in reporting, this occurs due to changes in boss fund management rules, and system changes. reporting.